2018
DOI: 10.1002/ijc.31301
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sex and efficacy of immune checkpoint inhibitors (PD‐1 and CTLA‐4 inhibitors)

Abstract: Immune checkpoint inhibitors (ICIs) exert the antitumor efficacy depending on immune response, which is affected by sex difference, where both biological and sociological factors are involved. The role of sex in ICI trials has been overlooked. How sex correlates with ICI efficacy is incompletely understood. Clinical trials evaluating ICI versus other therapies in male and female patients were included. The hazard ratio (HR) and 95% confidence interval (CI) of overall survival (OS) and progression-free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
74
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 30 publications
8
74
2
2
Order By: Relevance
“…The previous study indicated that men treated with PD‐1 inhibitor had two‐times lower the risk of death than women . The result was partly in accordance with Grassadonia’s study (male: HR 0.67, 95% CI 0.55‐0.80; female: HR 0.77, 95% CI 0.57‐1.05) and Wu’s study (male: HR 0.60, 95% CI 0.36‐0.84; female: HR 0.88, 95% CI 0.68‐1.08), which revealed no significant improvement in PFS in women in NSCLC . Therefore, it remains a controversy and under‐investigated issue whether magnitude of overall survival and progression‐free survival advantage from immunotherapy are sex‐dependent.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The previous study indicated that men treated with PD‐1 inhibitor had two‐times lower the risk of death than women . The result was partly in accordance with Grassadonia’s study (male: HR 0.67, 95% CI 0.55‐0.80; female: HR 0.77, 95% CI 0.57‐1.05) and Wu’s study (male: HR 0.60, 95% CI 0.36‐0.84; female: HR 0.88, 95% CI 0.68‐1.08), which revealed no significant improvement in PFS in women in NSCLC . Therefore, it remains a controversy and under‐investigated issue whether magnitude of overall survival and progression‐free survival advantage from immunotherapy are sex‐dependent.…”
Section: Discussionsupporting
confidence: 76%
“…It still remains unknown which is better efficacy of PD‐1, PD‐L1, or CTLA‐4 inhibitors for men and women. A previous meta‐analysis emphasized that PD‐1 inhibitors for men would consequently have better OS benefit than women . Our result indicated that women had a lower HR of OS meaning a higher magnitude of overall survival efficacy, but no significant PFS benefit from PD‐1 inhibitors.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations